2014
DOI: 10.1089/cap.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety of Stimulants in Children with Attention-Deficit/Hyperactivity Disorder: A Nationwide Prospective Cohort Study

Abstract: Objective: The purpose of this study was to determine whether stimulant users are at higher risk of a later cardiovascular event than are non-users, examining this association in both a national cohort and a population-based sample of children and adolescents diagnosed with attention-deficit/hyperactivity disorder (ADHD). We also aim to examine a possible doseresponse relationship in such an association. Methods: We conducted a longitudinal, prospective cohort study of all children born in Denmark between 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 43 publications
1
73
1
Order By: Relevance
“…Detection and diagnosis tend to be later and less frequent in females than in males, probably related to the observed lower levels of extroversion and aggression in females [13]. Girls diagnosed with ADHD are also less likely to be treated with medication than boys [15]. The awareness among clinicians that ADHD exists in adulthood is also often limited [16].…”
Section: Introductionmentioning
confidence: 99%
“…Detection and diagnosis tend to be later and less frequent in females than in males, probably related to the observed lower levels of extroversion and aggression in females [13]. Girls diagnosed with ADHD are also less likely to be treated with medication than boys [15]. The awareness among clinicians that ADHD exists in adulthood is also often limited [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although extremely rare, several large studies have indicated that there may be a doubling of such risk compared with nonusers. 24,25 Therefore, before starting a stimulant, PCPs should inquire about any patient history of structural heart defects, hypertrophic cardiomyopathy, arrhythmias (eg, prolonged QT syndrome), or sudden death in family members, especially at a young age. Questions should also be asked regarding any patient history of chest pain, syncope, exercise intolerance, or palpitations.…”
Section: Featurementioning
confidence: 99%
“…A separate prospective longitudinal cohort study of 714,258 Danish children containing 8300 diagnosed with having ADHD and followed for a mean of 9.5 years reported an increased overall rate of any CV event, that is, CV disease NOS, arrhythmias, and hypertension, in stimulant users vs. nonusers (Dalsgaard et al 2014). However, all observations of serious CV events (e.g., cardiac arrest, ischemic heart disease) or death due to any cause occurred in the nonstimulant users.…”
Section: Introductionmentioning
confidence: 99%